ChemInform Abstract: Na3SbSe3: Synthesis, Crystal Structure Determination, Raman Spectroscopy, and Ionic Conductivity. Issue 3 (22nd January 2013) - Pompe, Constantin; Pfitzner, Arno
Abstract Yellow single crystals of the title compound are prepared by solid state reaction of a stoichiometric mixture of anhydrous Na2Se, Sb, and Se in a 3:2:3 ratio (evacuated silica ampule, 723 K, 10 weeks).